Integrated Reporting and the Informativeness of Financial Analysts' Stock Recommendations - Baboukardos, Diogenis; Kopita, Anastasia (My University, 2024)
Synopsis The research problem The purpose of this study was to examine the market reaction to sell-side analyst recommendation revisions issued under an integrated reporting (IR) approach. Motivation Advocates of this corporate reporting approach argue that IR enhances capital markets' information environment by rendering investors better able to assess the value creation process of a firm. Recent empirical studies corroborate this argument. Considering the central role of financial intermediaries, we investigated whether the informativeness of analyst recommendation revisions is associated with the adoption of IR and the quality of integrated reports. The test hypotheses We tested whether the informativeness of analyst recommendation revisions decreases or increases after the mandatory adoption of an IR approach. Furthermore, we tested whether the informativeness is negatively or positively related to the quality of the released integrated report after the mandatory adoption of an IR approach. Target population We focused on the South African capital market, which is the only setting where IR is mandated. We utilized a sample of 3,201 recommendation revisions made within a 3-year window around the mandatory IR adoption. Adopted methodology This study used ordinary least square (OLS) regressions and applied difference-in-differences as well as instrumental variable approaches. Analyses We modeled the market reaction to the recommendation revisions as a function of the period in which the recommendations are announced (i.e., pre- or post-adoption), along with other factors affecting market reaction. In subsequent tests, we also modeled the market reaction to the recommendation revisions as a function of the quality of a firm's integrated report. Findings We found strong evidence that analysts' revisions exhibited economically and statistically significantly lower information content under IR. Moreover, we found that upgrades and downgrades issued in the post-adoption period were less informative when issued for firms with high-quality integrated reports. Overall, results showed that the benefit of acquiring advice from analysts became more marginal under an IR approach.
Keywords: analysts' recommendations; Integrated reporting; market reaction; South Africa